Kebijakan Dana Pemberdayaan 1% PT. Freeport Indonesia kepada Suku Amungme dan Kamoro Melalui LPMAK - Marey, Zakharias Frans (JURNAL EKOLOGI BIROKRASI, 2023)
Customary rights owners, investors and the state are working groups that must uphold the principles of justice in PTFI's mining business, the state, the Amungme and Kamoro communities are working partners in mining exploration in Mimika, Papua. Profit sharing between parties I, II and III is regulated in a humane work agreement and no injustice should occur. However, the problem is that customary landowners only receive a partnership trust budget (social budget), which varies annually. For example, from 1994-2003 or 23 years of existence, the social budgeting distribution from PTFI amounted to 1.3 billion US dollars (managed by LPMAK). Partnership budget distributions of $634 and $662 million also occurred (managed by PTFI's Non Community Affair Dept.). Trust and partnership budget reached USD 437.3 in 2006 and 2007 increased to USD 480.3 also distributed by PTFI. Decreased, reaching USD 400.0 in 2010. This research has both academic and practical purposes. It is useful for socially just budget distribution. Then, the methodology used is descriptive qualitative. Data collection was done through direct and indirect interviews. Samples, data analysis and management were conducted on the Amungme and Kamoro tribes as customary rights owners in Mimika, Papua. Research findings; PTFI, the state, the Amungme and Kamoro communities are not good partners in the mining business in Mimika, Papua.